Konservasi Levine Di Puskesmas Kesamben Kabupaten Jombang - Alik Septian Mubarrok (Fakultas Ilmu Kesehatan, 2018)
Management of diabetes mellitus requires active awareness from patients, families and the community. To achieve empowerment in behavior change, it is necessary to improve education and comprehensive motivation. One of them is the empowerment of Posbindu cadres in each region, this needs to be done to improve the ability of Posbindu cadres in order to manage and run health service work, especially in the delivery of information or education to the community. This study is a quasi-experimental study with a pretest posttest control group design. The treatment group was given treatment namely health education in accordance with the levine conservation theory then in the control group no treatment was given. The results of the study showed that there were significant differences in self efficacy and Self Care Activity in the treatment and control groups. The results of data analysis with independent t test self efficacy obtained t value 24,057 (p = 0,000), in the Self Care Activity the value of t is 26,670 (p = 0,000). The conclusion is that the health education treatment with the Levine Conservation method gives significant results to the increase in self efficacy & Self Care Activity of type 2 DM patients, the Levine Conservation model is able to make individuals improve cognitive, affective, motivational, and health behaviors of patients with type 2 diabetes.